Molecular Detection of Candidatus Rickettsia andeanae and Ehrlichia sp. in Amblyomma pseudoconcolor Aragão, 1908 (Acari: Ixodidae) from the Argentinian Patagonia - Sebastian, Patrick; Winter, Marina; Abate, Sergio Damián; Tarragona, Evelina Luisa; Nava, Santiago (MDPI, 2022)
This study presents the molecular detection of Candidatus Rickettsia andeanae and Ehrlichia sp. in Amblyomma pseudoconcolor Aragão, 1908 (Acari: Ixodidae) collected on a large hairy armadillo (Chaetophractus villosus (Desmarest, 1804)). On 12 October 2020, a specimen of C. villosus was found dead on the road in Río Negro province, Argentina. Molecular detection of Rickettsia and Ehrlichia agents was performed amplifying the gltA and 16S rRNA gene, respectively. One tick, determined morphologically and genetically as A. pseudoconcolor, was collected on C. villosus. The rickettsial agent detected in A. pseudoconcolor was identified as Candidatus Rickettsia andeanae. The Ehrlichia sp. strain showed high sequence similarity to different uncultured Ehrlichia sp. detected in horses, capybaras and Ixodes ornithorhynchi from Nicaragua, Brazil and Australia, respectively. The results of this study and previous findings suggest that A. pseudoconcolor may be a potential vector of some Rickettsia and Ehrlichia bacteria of unknown pathogenicity.